Freud's last session [videorecording (DVD)] - Brown, Matthew (Film director); St. Germain, Mark; Hopkins, Anthony, 1937-; Goode, Matthew, 1978-; Fries, Liv Lisa, 1990-; Balfour, Jodi, 1987-; Northam, Jeremy, 1961-; Brady, Orla, 1961- (Sony Pictures Home Entertainment, 2024)
Freud invites iconic author C.S. Lewis to debate the existence of God. And his unique relationship with his daughter, and Lewis' unconventional relationship with his best friend's mother.